PENGARUH KOMPETENSI DAN KOMPENSASI TERHADAP KINERJA DENGAN MEDIASI KEPUASAN KERJA (Students' Journal of Accounting and Banking, 2012)
This study aimed to determine the effect of competencies and compensation to the performance with mediate on the job satisfaction. Total population of as many as 443 people with a total sample of 110 people. The sampling technique used was purposive sampling. With a Cronbach alpha reliability test, regression analysis, t test, and a test with an adjusted R square r. The results show that competence has positive and significant impact on job satisfaction. Compensation and significant positive effect on job satisfaction. Competence has positive and significant effect on performance. Compensation and significant positive effect on performance. Job satisfaction is a positive and significant effect on performance. Job satisfaction did not mediate the effect of competence on employee performance. Job satisfaction did not mediate the effect of compensation on performance. Keywords: Competence, compensation, job satisfaction and performance.